Pharmacokinetics of oral tenofovir disoproxil fumarate in pregnancy and lactation: a systematic review - Marieke Bierhoff (2020)
BACKGROUND: Tenofovir disoproxil fumarate (TDF), the oral prodrug of tenofovir (TFV), is advocated in pregnancy for prevention of mother-to-child transmission (PMCT) with failure of hepatitis B immunoglobulin and vaccination. The pharmacokinetics of TDF monotherapy for PMCT-HBV is important if deployment is to emulate the success of multiple antiretrovirals (ARVs) for PMCT-HIV in resource-constrained settings. METHODS: This systematic review followed a protocol and is reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (PRISMA) guidelines. We included studies that enrolled pregnant women who received oral TDF therapy as monotherapy or in combination with other ARVs: irrespective of the reason for receiving the drug (for example, HIV, HBV or pre-exposure prophylaxis); and reported pharmacokinetics. RESULTS: The area under the concentration-time curve (AUC), maximum plasma concentrations (Cmax) and last measurable plasma concentration (Clast) of TFV were decreased in the second and third trimester compared with first trimester or post-partum. In none of the manuscripts was the non-pregnant HBV threshold of Cmax of 300 ng/ml reached, but the 50% effective concentration (EC50) of TFV is lower for treatment of HBV compared with HIV. The TFV concentration in breastfed infants was 0.03% of the recommended infant dose. CONCLUSIONS: Most knowledge of pharmacokinetics of TFV in pregnancy results from studies on HIV involving multiple ARVs. Increased TFV clearance occurred in the second and third trimester when optimal TFV concentrations are required to maximize suppression of HBV in the window before birth. Dose or duration adjustments will be better conceptualized with concurrent analysis of the pharmacokinetics of TFV monotherapy and hepatitis B pharmacodynamics in pregnancy.